(untitled) (International Journal of Innovative Technologies in Economy, 2023)
Population aging presents numerous challenges, such as a reduced fiscal balance, changes in the savings patterns of households, and higher age dependency ratios. These consequences are evident for older individuals, the government, and the economy at large. This study examined the impact of population aging on the economic growth of South Africa, studying the King Cetshwayo District Municipality specifically. A panel data set for the period 2002-2020 by Quantec Easy Data was used for the study. A FE regression model was used to examine the relationship between economic growth (GDP per capita), population aging, savings, education, and other independent variables. The findings from the panel data analysis revealed that population aging negatively affects economic growth only in the short run but not in the long run. Also, other factors like education, savings, and income affected economic growth in the King Cetshwayo District Municipality. This study recommends a transformation in the country’s savings by educating the population about the importance of savings in order to improve GDP per capita and the economic wellbeing of the people.